Predictive Factors for Metastatic Infection in Patients With Bacteremia Caused by Methicillin-Sensitive Staphylococcus aureus. (January 2015) - Horino, Tetsuya; Sato, Fumiya; Hosaka, Yumiko; Hoshina, Tokio; Tamura, Kumi; Nakaharai, Kazuhiko; Kato, Tetsuro; Nakazawa, Yasushi; Yoshida, Masaki; Hori, Seiji
Abstract: Background: Metastatic infections such as infective endocarditis and psoas abscess are serious complications of Staphylococcus aureus bacteremia because failure to identify these infections may result in bacteremia relapse or poor prognosis. In the present study, we determined the predictive factors for metastatic infection due to methicillin-sensitive S. aureus bacteremia. Methods: A retrospective cohort study was conducted among patients with methicillin-sensitive S. aureus bacteremia at the Jikei University Hospital between January 2008 and December 2012. Factors analyzed included the underlying disease, initial antimicrobial treatment and primary site of infection. Results: During the 5-year study period, 73 patients met the inclusion criteria and were assessed. The most common primary site of bacteremia was catheter-related bloodstream infection (25/73 [34.2%]). Metastatic infection occurred in 14 of 73 patients (19.2%) (infective endocarditis [3], septic pulmonary abscess [3], spondylitis [4], psoas abscess [4], epidural abscess [3] and septic arthritis [1]). Six patients had multiple metastatic infections. Multivariate analysis revealed that the predictive factors associated with the development of metastatic infection were a delay in appropriate antimicrobial treatment of >48 hours, persistent fever for >72 hours after starting antibiotic treatment and lowest C-reactive protein levels of >3 mg/dL during 2 weeks after the onset of bacteremia. Conclusions: This study demonstrated that additional diagnostic tests should be conducted to identify metastatic infection, particularly in patients with delayed antimicrobial treatment, persistent fever and persistently high C-reactive protein levels.